Implementation Of Minimum Health Service Standards For Maternal And Child Health (Mch) And Family Planning In Bengkayang District, Indonesia - Karolina, Maria Estela; Santoso, Ferry; Sebong, Perigrinus Hermin; Hidayanti, Maria Ulfa Nur (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: Primary Healthcare Centers, or Puskesmas, are vital in delivering the Minimum Health Service Standard (MHSS) for maternal and child health. This study aims to analyze the performance outcomes of maternal and child health services based on MHSS and to identify the health worker and socio-demographic factors that influence MHSS achievement in Bengkayang District. Method: This study utilized two approaches: cross-sectional exploration and situational analysis based on reviews at the health management level and health service units in the district. It was conducted from August to October 2020 at three Primary Healthcare Centers in Bengkayang District, utilizing purposive sampling and involving 20 key informants. Results: The MHSS’s achievements in maternal and child health services and family planning programs varied. The K4 coverage at Puskesmas Ledo fell short of its target. Additionally, the percentage of childbirths assisted by health workers in the health facilities at Puskesmas Bengkayang, Ledo, and Jagoi Babang did not meet the national MHSS target. Coverage for the initial antenatal care visit and essential immunization targets at Puskesmas Ledo and Jagoi Babang also did not reach the national benchmarks. Furthermore, family planning service coverage at Puskesmas Jagoi Babang did not meet the established target, and the family planning data at Puskesmas Ledo was incomplete. Conclusion: The performance of MHSS in the Bengkayang District requires improvement. Additional efforts should encourage community engagement and partnerships to guarantee that trained health workers assist with all birth deliveries in health service facilities. The Puskesmas should also revise its recording and reporting processes related to family planning service indicators.